Ethical Values of Advertising in Print and Electronic Media (A Study on Fairness Products in Visakhapatnam City) - Mohideen, A. K. (Indian Journal of Marketing, 2009)
Advertising is one of the most powerful marketing tools which enhances communication by connecting the company with the customers. Moral and ethical standards were proposed to restrict the range of products, services and practices that can be advertised. Nevertheless, the problem still persists. One of the questions discussed while analyzing the ethical aspects of advertising is the use of fear appeals and threat to popularize a certain product, concept etc., or to boost up the sales. The idea of using fear to advertise a certain product is viewed as unethical if the solutions that are advertised cannot eliminate the threat presented. This holds true as long as advertisers show the consequences of not paying heed to the recommendations offered in the advertisement. Furthermore, using fear appeals and threats is considered unethical as they might create unnecessary anxiety among potential customers. However, some people support the idea of using fear for marketing purposes. They claim that such advertisements reflect the norms of a certain society.